2018
DOI: 10.1186/s40249-018-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus among street children in Iran

Abstract: BackgroundStreet children are forced to spend a lot of time away from their homes and some of them do not have homes at all, due to economic and family problems, which makes them exposed to many health problems, such as the hepatitis C virus (HCV) infection. Iran, like many other countries in the world, experiences the burden of street children, however, the rate of HCV among street children is virtually unknown. This study aimed to determine the prevalence of HCV among street children in Iran.Main bodyThis sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The findings of this study showed that the prevalence was 47%. This was higher than the prevalence of HCV among prisoners (28%) [67], thalassemia patients (19%) [68], street children (2.4%) [69], blood donors (0.5%) [70] and the general population (0.6%) [14]. This high rate confirms that, as it is well-known, PWID are one of the most important and high-risk groups for developing HCV [2,71].…”
Section: Discussionmentioning
confidence: 63%
“…The findings of this study showed that the prevalence was 47%. This was higher than the prevalence of HCV among prisoners (28%) [67], thalassemia patients (19%) [68], street children (2.4%) [69], blood donors (0.5%) [70] and the general population (0.6%) [14]. This high rate confirms that, as it is well-known, PWID are one of the most important and high-risk groups for developing HCV [2,71].…”
Section: Discussionmentioning
confidence: 63%
“…HBcAb, and seven (3.5%) cases for HCVAb. A meta-analysis estimated the prevalence of HCV infection among street children in Iran 2.4% (12). The differences in the results of the studies mentioned above may be due to the following reasons: differences in nationality (the studied population was Afghan) and differences in sampling locations.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that strict HCV screening of donated blood units since 1996, performing harm reduction programs for people who inject drugs (PWID), the early finding of HCV-seropositive individuals, and treatment of the patients with the low-cost generic direct-acting antiviral drugs are the most critical factors associated with the lower rate of this infection in Iran (3). On the other hand, much higher rates of HCV infection were estimated among Iranian populations at intermediate to high risk of exposures such as PWID (41 -47%) (5-7), prisoners (22 -28%) (6,8,9), hemodialysis patients (11%) (10), people who use but not inject drugs (8%) (6,7), female sex workers (8%) (6), and homeless children (2%) (11).…”
Section: Introductionmentioning
confidence: 99%